2020
DOI: 10.25259/jcis_67_2019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Prevalence and Morphological Characteristics of Bifid Mandibular Canal Using Cone-Beam Computed Tomography – A Retrospective Cross-Sectional Study

Abstract: Objectives: To evaluate the prevalence, location and configuration of bifid mandibular canals so as to avoid injury to the nerve and inadequate anesthesia during surgical procedures. Materials and Methods: CBCT scan of 203 patients (125 males and 78 females) was evaluated for the presence and the type of the bifid mandibular canal. They were classified according to Nortje et al. The prevalence rates were determined according to gender, location, and type of bifid mandibular canal. Statistical analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Taking into account the classification by Naitoh et al (2009) [13], performed according to data obtained by CBCT images, this anatomical variant falls into type IV BMCs: buccolingual canals, lingual variant, originating in the lingual wall of MC, a rare variant, present in 1.8% of cases, according to Naitoh et al (2009) [13], in 9.7% of cases, as stated by Okumuş & Dumlu (2019) [14], in 10.6% of cases, in accordance with Kuribayashi et al (2010) [6,15] and in 14.3% (4.76% buccal canal and 9.5% lingual canal) of cases, as reported by Nithya & Aswath (2020) [8].…”
Section:  Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Taking into account the classification by Naitoh et al (2009) [13], performed according to data obtained by CBCT images, this anatomical variant falls into type IV BMCs: buccolingual canals, lingual variant, originating in the lingual wall of MC, a rare variant, present in 1.8% of cases, according to Naitoh et al (2009) [13], in 9.7% of cases, as stated by Okumuş & Dumlu (2019) [14], in 10.6% of cases, in accordance with Kuribayashi et al (2010) [6,15] and in 14.3% (4.76% buccal canal and 9.5% lingual canal) of cases, as reported by Nithya & Aswath (2020) [8].…”
Section:  Discussionmentioning
confidence: 84%
“…When the presence of a BMC is identified, with possible origin located above the conventional anesthesia site commonly used (the mandibular foramen), Gow-Gates or Akinosi anesthesia techniques are recommended for inferior alveolar nerve block; however, these techniques must be performed only when traditional local anesthesia proves ineffective [8,14,16]. In the clinical case described, we opted for the Gow-Gates technique, in accordance with Lew & Townsen (2006) observations, who showed that this anesthesia technique is more effective for blocking the accessory nerve branches, proximal to their place of origin [22].…”
Section:  Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of a small and variable in terms of structure and course of the retromolar canal was possible thanks to the intensive development of imaging studies, especially computed tomography (CT) and cone beam computed tomography (CBCT) [9]. In some patients, the retromolar canal is already visible on the panoramic image, although this technique reveals only small percentage of the retromolar canals [10].…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, CBCT has also been suggested for a meticulous assessment and identification of bifid mandibular canals before any surgical intervention to decrease or avoid postoperative sequelae. 19 Authors also favor the provision of conebeam CT when clinicians find one or more signs of close proximity between the roots of the tooth and the mandibular canal in the two-dimensional (2D)imaging or if CBCT may change the treatment plan and in turn, the outcome of the procedure for the patients. Further research on high-evidence levels is suggested.…”
Section: Discussionmentioning
confidence: 99%